Análise dos processos de alagamento e inundação da bacia do Córrego Mirassol, em Rio Claro-SP - Montanha, Alexandre Lombardo [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
With the increasing urbanization of Rio Claro, the high rate of waterproofing of the soil, besides the alteration of the local natural landscape, problems of floods and floods became recurrent in the city, the research in question aimed to give a focus to the Stream of the Córrego Mirassol, that was divided in sectors being them the Córrego Mirassol together with the Lagoa da Cerâmica Wenzel, in such a way that lagoon was in its great part grounded with the presence of drains that are created to facilitate the water flow for the remaining parts of that lagoon, the Lagoa do Wenzel together with the Lagoa do Cerâmica Wenzel, where the first one, which operated as a damping area, damming some of the water, was also grounded due to this urbanization, thereby increasing the speed of water flow, also being built drains to facilitate this outflow, and the area of Jardim São Paulo overlooking the Av. Castello Branco that suffers erosion at the margin s of these drains, with even presence of rocky outcrops, drains that have undergone a widening, transforming that area into a water retention site, arriving at an area of bottleneck, resulting in flooding and flooding. Thus, this report seeks to carry out an analysis to better understand the causes and consequences of the flooding processes that occur there, also proposing solutions to minimize or inhibit the occurrence of these problems. For that, a field work was carried out to collect information and data, and to carry out an analysis of the current local situation. In addition, data processing and modeling techniques were used to systematize the data and help in understanding the causes of the same, with the generation of declivity maps, susceptibility to flooding, among others. It is thus proposed the implantation of a Linear Park following the flow of the channel, so that it would protect the place of the indicated effects

Com a crescente urbanização de Rio Claro, a alta taxa impermeabilização do solo, além da alteração da paisagem natural local, os problemas de inundações e alagamentos se tornaram recorrentes na cidade, a pesquisa em questão visou dar um enfoque para a Bacia do Córrego Mirassol, que foi dividida em setores sendo eles o Córrego Mirassol juntamente com a Lagoa do Cerâmica Wenzel, de forma que tal Lagoa foi em sua boa parte aterrada com a presença de drenos que são criados para facilitar o escoamento de água para as partes remanescentes dessa lagoa, a Lagoa do Wenzel juntamente com a Lagoa do Cerâmica Wenzel, em que a primeira, que funcionava como uma área de amortecimento, represando parte da água, também foi aterrada por conta dessa urbanização, com isso aumentando a velocidade de escoamento de água, também sendo construídos drenos para o facilitar desse escoamento, e a área do Jardim São Paulo a juzante da Av. Castello Branco que sofre com a erosão nas margens desses drenos, com presença até mesmo de afloramentos rochosos, drenos esses que passaram por um alargamento, transformando aquela área em um local de represamento de água, chegando então à uma área de estrangulamento, resultando na ocorrência de alagamentos e inundações. Dessa forma, tal relatório busca efetuar uma análise para melhor compreensão das causas e consequências dos processos de inundação que ali ocorrem, propondo também soluções para minimizar ou inibir a ocorrência desses problemas. Para isso, foi realizado um trabalho de campo para coleta de informações e dados, e a realização de uma análise da situação atual local. Além disso, foram utilizadas técnicas de processamento e modelagem de dados para uma sistematização dos dados e auxilio na compreensão das causas do mesmo, com a geração de mapas de declividade, susceptibilidade à inundação, entre outros. Sendo proposto assim, a implantação de um Parque Linear...
Keywords: Geografia ambiental; Inundações; Urbanização; Rio Claro (SP)